Religious Based Social Services on Rehabilitation of Schizophrenic Patients - Soetji Andari (Jurnal Penelitian Kesejahteraan Sosial, 2017)
Schizophrenia is a complex mental disorder in which a person experiences difficulties in thought processes leading to hallucinations, delusions, thought disorder. Treatment committed on persons with schizophrenia after three months of therapy at the rehabilitation center sufisti- psychiatric hospital, made their conditions become better, which was originally their behavior unstable with often talking to himself, then gradually recovered. This research is a qualitative descriptive through observation in one of the Boarding Schools in Demak which handles clients with schizophrenia. Interviews and observations on 37 clients conducted with a wide range of backgrounds problems. Of the 255 clients who are in rehab cottage â€œNurussalamâ€. Healing Model conducted by boarding ngepreh is an alternative treatment method with Hydro Therapy Method(religious therapy and herbal therapy) for clients with schizophrenia, the healing is still relatively rare and worth replicated elsewhere. The family as a supporter of healing have a strong conviction to help heal patients with psychotic disorders, other than that there is cooperation between the therapist and the client, the desire of the client to heal, an atmosphere of togetherness with affection and kinship. The amount of family support clients, greatly help in the smooth process of healing.